Physicochemical and Sensory Characteristics of Sausage made of Spent Hen Meat Fortified with Carrot (Daucus carota L) Paste - Palandeng, Feriana C.; Mandey, Lucia C.; Lumoindong, Frans (Pascasarjana Unsrat, 2016)
Sausage spent hen meat is one of processed protein product alternatives of animal origin. The purposes of this study were to find out the best formulation of culled laying hens sausage using mixture of carrot paste and baruk sago as filler and to evaluate the physical, chemical and functional characteristics of the sausage. The research consisted of five treatments of filler using various mixtures carrot paste and baruk sago, namely: 0%, 5%, 10%, 15% and 20% of carrot paste of the total 25% filler. The results showed that the use of carrots paste in the filler significantly improved (P < 0.05) the physical characteristics that increase the value and tenderness of the sausage cooking shrinkage. The chemical characteristics, on the other hand, indicated that moisture, protein, fat and carbohydrate contents were significantly affected, whereas ash content was not. The Î²-carotene content of sausage increased with the increasing consentration of carrot paste in the filler mixture. Sensory analysis showed that percentage of carrot paste in filler mixture only significantly affected flavor and texture but did not significantly affect the color and aroma of sausage. The hightest average panelists score was found in P2 formulation of 10% carrot and 15% sago. The water, ash, protein, fat, carbohydrate, and Î²â€“carotene contents of the P2 formula sausage were 60.63 %, 1.82 % , 15.72 %, 12.24 %,Â 8.25% and 0.04 % , respectively. Keywords: sausage, culled laying hens, carrots, sago baruk, physicochemical, sensory